Management of Ineffective Esophageal Hypomotility - Jandee, Sawangpong; Geeraerts, Annelies; Geysen, Hannelore; Rommel, Nathalie; Tack, Jan; Vanuytsel, Tim (Frontiers in Pharmacology, 2021)
Esophageal hypomotility in general and especially ineffective esophageal motility according to the Chicago criteria of primary motility disorders of the esophagus, is one of the most frequently diagnosed motility disorders on high resolution manometry and results in a large number of patients visiting gastroenterologists. Most patients with esophageal hypomotility present with gastroesophageal reflux symptoms or dysphagia. The clinical relevance of the motility pattern, however, is not well established but seems to be correlated with disease severity in reflux patients. The correlation with dysphagia is less clear. Prokinetic agents are commonly prescribed as first line pharmacologic intervention to target esophageal smooth muscle contractility and improve esophageal motor functions. However, the beneficial effects of these medications are limited and only confined to some specific drugs. Serotonergic agents, including buspirone, mosapride and prucalopride have been shown to improve parameters of esophageal motility although the effect on symptoms is less clear. Understanding on the complex correlation between esophageal hypomotility and esophageal symptoms as well as the limited evidence of prokinetic agents is necessary for physicians to appropriately manage patients with IEM.